2017
DOI: 10.1111/anae.13837
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy, intra- and inter-rater reliability of three scoring systems for the glottic view at videolaryngoscopy

Abstract: SummaryAn accurate and reproducible recording of laryngoscopic view at tracheal intubation is an important aspect of anaesthetic practice. Unlike direct laryngoscopy, in which the view achieved by the line of sight directly relates to the ease of intubating the trachea, videolaryngoscopy can create a situation in which the view is good, but intubation difficult or impossible. Communicating this to a subsequent anaesthetist is important. We compared three scoring systems: Cormack and Lehane; POGO (percentage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 21 publications
0
29
0
Order By: Relevance
“…The two groups did not differ in terms of age, sex, BMI, mouth opening, neck extension, degree of retrognathia, Mallampati grade, the presence of nasal or oral anatomical abnormalities or best glottic view (Cormack and Lehane). Although glottic views are likely better described by other scoring systems [19], Cormack and Lehane grading was used due to provider familiarity. Learners who performed the intubations were primarily anaesthesia residents, of whom the majority were in their first year of clinical anaesthesia training.…”
Section: Resultsmentioning
confidence: 99%
“…The two groups did not differ in terms of age, sex, BMI, mouth opening, neck extension, degree of retrognathia, Mallampati grade, the presence of nasal or oral anatomical abnormalities or best glottic view (Cormack and Lehane). Although glottic views are likely better described by other scoring systems [19], Cormack and Lehane grading was used due to provider familiarity. Learners who performed the intubations were primarily anaesthesia residents, of whom the majority were in their first year of clinical anaesthesia training.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, Cormack-Lehane grade II can correspond to a view of almost the entire glottis or to only a tiny part of it, and so cannot serve predict easy or difficult intubation 24. Laryngoscopy attempts, use of external laryngeal manipulation and use of ancillary equipment are also reported in order to concretely describe the ease of intubation assessed, for example, by the Fremantle score in O’Loughlin et al 15. The laryngoscopy attempts was not chosen as the primary outcome because we doubted that it would make a significant difference with this outcome as most of intubation requires only one laryngoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Here, then, the choice of the better view captured to establish the POGO score is left to the anaesthetist incharge of the direct laryngoscopy who is unblinded to the allocation group. Regarding the use of videolaryngoscopy, the laryngeal exposure score can differ between direct laryngoscopy and videolaryngoscopy: in direct laryngoscopy, the view achieved by the line of sight correlates directly to the ease of intubating the trachea, as videolaryngoscopy can create a situation in which the view is good but intubation is difficult or impossible 15. This type of system was not included in the InSize25 trial design in order to ensure better feasibility among multiple centres.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though the use of videolaryngoscopy is associated with an improved view of the glottis, the process of placing a tracheal tube can take longer and be more difficult . In the context of paediatric intubation with an unchannelled videolaryngscope, we have found that adding lateral curvature of the distal tube to proximal anterior curvature using a stylet creates an S shape, enabling more precise manipulation of the tracheal tube in all three dimensions and easier placement (Fig.…”
mentioning
confidence: 99%